The Impact of Online Social Media Use on the High Prevalence of Cyberbullying Behavior Among Students at SMAN 3 Selong, East Lombok Regency - Irvina Astrini Arianti; Muh. Zubair; M. Samsul Hadi (STKIP Taman Siswa Bima, 2025)
This study aims to examine the impact of online social media use on the increasing prevalence of cyberbullying behavior among students at SMAN 3 Selong, East Lombok Regency. The rising intensity of social media usage among teenagers highlights the urgency to investigate its effects, particularly on psychosocial aspects and peer interaction. This research employs a descriptive qualitative approach, utilizing closed-ended questionnaires and in-depth interviews with guidance and civics teachers. The findings reveal that most students are involved in cyberbullying, either as victims, perpetrators, or bystanders. High social media usage especially during nighttime and compulsive behavior to check social platforms significantly influence students’ emotional states and increase the risk of online conflict. These results emphasize the importance of strengthening digital literacy education and character development as preventive measures. In conclusion, uncontrolled use of social media contributes to the high incidence of cyberbullying among students, thereby demanding greater attention from schools, parents, and the broader community